2021
DOI: 10.3390/vetsci8110244
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of N-acetylcysteine in Healthy and Mycoplasma gallisepticum-Infected Chickens

Abstract: N-acetylcysteine (NAC) is widely used as a mucolytic agent in cases with inflammation of the lungs. NAC is applied in poultry with aflatoxin B1 intoxication as an antioxidant, but its pharmacokinetics are not known. The present study was conducted to characterize the population pharmacokinetics of orally administered NAC in broilers. It included 32 chickens, divided into four groups, treated with NAC at a dose rate of 100 mg/kg/day mixed with the feed: healthy broilers (n=6); chickens infected with Mycoplasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 29 publications
4
11
1
Order By: Relevance
“…In the current investigation, the results about the recovery were in accordance with data reported for human plasma: 100.8-112.7% for a concentration range of 0.01-5 μg/ml (Lu et al, 2011). Similar values were found for chicken plasma: 98.51-101.88% for a concentration range of 0.25-10 μg/ml (Petkova & Milanova, 2021).…”
Section: Calibration Curvessupporting
confidence: 91%
See 4 more Smart Citations
“…In the current investigation, the results about the recovery were in accordance with data reported for human plasma: 100.8-112.7% for a concentration range of 0.01-5 μg/ml (Lu et al, 2011). Similar values were found for chicken plasma: 98.51-101.88% for a concentration range of 0.25-10 μg/ml (Petkova & Milanova, 2021).…”
Section: Calibration Curvessupporting
confidence: 91%
“…The LC-MS/MS method for quantitative analysis of NAC was validated according to the accepted criteria for accuracy, precision, sensitivity and recovery in the Guidelines on Bioanalytical Method Validation of European Medicine Agency (EMA, 2011). Our previous experiments showed that plasma levels of NAC after oral administration at a dose rate of 50 mg/kg/12 h with the feed were very low: 2.26 ± 0.91 μg/ml (Petkova & Milanova, 2021), around 10-fold lower in comparison with those in cats (Basu et al, 2012). In order to clarify the observed results, a classical pharmacokinetic investigation with intravenous and intraingluvial administration of NAC is required.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations